EVALUATION OF ANTIMICROBIAL ACTIVITY OF THE DIFFERENT CULTURE EXTRACTS OF CYANOBACTERIAL SPECIES - T. MALATHI; M. RAMESH BABU; D. SRINIVAS; B. DIGAMBER RAO (International Journal of Pharma and Bio Sciences, 2016)
The main aim of the present investigation was to assess the efficacy of the antimicrobial activity of Anabaena circinalis, Nostoc muscorum, Stigonema ocellatum and Hapalosiphon welwitschii. The antimicrobial activity of cyanobacterial species were screened by using Agar disc diffusion method against pathogenic bacteria and fungi. Chloroform extract of A. circinalis was resulted the highest antibacterial activity 21.00 ± 0.57 mm against E. coli followed by K. pneumonia. Similarly, highest antifungal activity 15.00 ± 1.15 mm was recorded with N. muscorum followed by S. ocellatum and A. circinalis against Trichophyton mentagrophytes, Aspergillus fumigatus and Aspergillus niger respectively. Chloroform extract was showed highest antimicrobial activity among all the solvents tested; ethyl acetate and methanol were the next preferred solvents. Statistical analysis of the data showed a significant (P ≤0.05) difference between the different solvents, cyanobacterial species against bacteria and fungi tried. In conclusion the present investigation suggested that cyanobacteria used as a potential natural drug sources owing to the antimicrobial efficiency.